The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4103/0301-4738.81047
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of hydrogel exoplant into upper eyelid 16 years after a scleral buckle procedure

Abstract: Sixteen years after scleral buckle surgery with a hydrogel episcleral exoplant, a 43-year-old woman presented with progressive binocular diplopia, ptosis, and an expanding mass in her upper eyelid. She underwent surgical removal of the hydrogel exoplant through an anterior approach. The exoplant proved to be friable, fragmented, and encapsulated in a fibrous tissue; the exoplant was removed in its entirety. Postoperatively, the eyelid mass resolved, while her diplopia and ptosis improved slightly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Whilst it is important to remove all of the foreign material at the time of surgery, it does not appear to matter if some capsular elements are left behind. 8,9 The cause of the bony defect in this patient remains uncertain but is likely secondary to a prior spontaneous bony dehiscence of the sinus floor predisposing to rupture of the overlying sinus mucosa during irrigation. Such defects can usually be detected by a careful review of the CT scans preoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…Whilst it is important to remove all of the foreign material at the time of surgery, it does not appear to matter if some capsular elements are left behind. 8,9 The cause of the bony defect in this patient remains uncertain but is likely secondary to a prior spontaneous bony dehiscence of the sinus floor predisposing to rupture of the overlying sinus mucosa during irrigation. Such defects can usually be detected by a careful review of the CT scans preoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…[17][18][19][20] Extruded portions of the device may present as eyelid masses. 18,19 Although the extrusion is clinically evident, there is likely concomitant intrusion or erosion into the globe ( Figure 4). Therefore, comprehensive assessment via radiographic imaging is recommended to identify more serious complications.…”
Section: Extrusion and Intrusionmentioning
confidence: 99%
“…A large study of 386 patients with hydrogel scleral buckles found that 1.3% of cases required explantation. 2 Other severe complications include implant expansion and fragmentation, 35 orbital pseudo-cellulitis, 6 orbital pseudotumor, 69 diplopia, 3,4,7,8 ptosis, 3 anterior erosion through the orbital septum and orbicularis oculi muscle, 10 spontaneous expulsion from the eye, 11 and infection of the scleral buckle. 12 …”
Section: Introductionmentioning
confidence: 99%